Study on the effect of PEG in ionic transport for CMC-NH4Br-based solid polymer electrolyte - N. K., Zainuddin; N. M. J., Rasali; Ahmad Salihin, Samsudin (Springer Berlin Heidelberg, 2018)
The present study investigates the ion transport properties and structural analysis of plasticized solid polymer electrolytes (SPEs) based on carboxymethyl cellulose (CMC)-NH4Br-PEG. The SPE system was successfully prepared via solution casting and has been characterized by using electrical impedance spectroscopy (EIS), Fourier transform infrared (FTIR) spectroscopy, and x-ray diffraction (XRD) technique. The highest conductivity of the SPE system at ambient temperature (303 K) was found to be 1.12 × 10−4 S/cm for un-plasticized sample and 2.48 × 10−3 S cm−1 when the sample is plasticized with 8 wt% PEG. Based on FTIR analysis, it shows that interaction had occurred at O–H, C=O, and C–O moiety from CMC when PEG content was added. The ionic conductivity tabulation of SPE system was found to be influenced by transport properties and amorphous characteristics as revealed by IR deconvolution method and XRD analysis.